Using Codes of Conduct to Resolve Legal Disputes - Aiken, Peter; Stanley, Robert M; Billings, Juanita; Anderson, Luke (Computer (Long Beach, Calif.), 2010)
In the absence of other published standards of care, it is reasonable for contractual parties to rely on an applicable, widely available code of conduct to guide expectations. The authors illustrate the current application of CoCs with a fictional enterprise resource planning (ERP) system implementation failure that is a compilation of real-life cases. Subject to binding panel arbitration, the plaintiff and defendant in the case presented conflicting interpretations of the same facts: From the plaintiff's perspective, the defendant failed to migrate the ERP system as promised; the defendant countered that defective and poor-quality data delayed the migration. Using the ACM/IEEE-CS CoC as a reference, expert testimony convinced the arbitration panel that the defendant's position was untenable, and the panel accordingly awarded the plaintiff a multimillion-dollar judgment.